Performance analysis of TCP over satellite channels - Gui, Tang Guan. (2008)
TCP/IP is a set of transmission standards which enables computers from multiple vendors running on different operating systems to share resources across the Internet. The performance of TCP/IP varies when the transmission path is a satellite link instead of terrestrial one. The transmission efficiency generally degrades in the satellite network due to high bandwidth-delay products, slow starts and congestion control algorithms. In this project the TCP/IP performance over the satellite network is investigated using experimental network configurations. The satellite and terrestrial network performances are compared. Some recommendations are provided to enhance the performance of the satellite network using TCP/IP.